2016
DOI: 10.1136/svn-2016-000016
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate management of asymptomatic carotid stenosis

Abstract: With modern intensive medical therapy, the annual risk of ipsilateral stroke in patients with asymptomatic carotid stenosis (ACS) is now down to ∼0.5%. Despite this, there is a widespread practice of routine intervention in ACS with carotid endarterectomy (CEA) and stenting (CAS). This is being justified on the basis of much higher risks with medical therapy in trials conducted decades ago, compared with lower risks of intervention in recent trials with no medical arm. Such extrapolations are invalid. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 53 publications
3
54
0
2
Order By: Relevance
“…However, evidence to date [39,40] has shown that natural history of asymptomatic CS has improved significantly with modern BMT, and routinely treating asymptomatic patients with CR, considered by degree of stenosis, is not reliable. Annual stroke risk of CR was similar to modern BMT while there were periprocedural risks in CR but not in BMT.…”
Section: Decision-making On Management Of Carotid Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence to date [39,40] has shown that natural history of asymptomatic CS has improved significantly with modern BMT, and routinely treating asymptomatic patients with CR, considered by degree of stenosis, is not reliable. Annual stroke risk of CR was similar to modern BMT while there were periprocedural risks in CR but not in BMT.…”
Section: Decision-making On Management Of Carotid Stenosismentioning
confidence: 99%
“…Annual stroke risk of CR was similar to modern BMT while there were periprocedural risks in CR but not in BMT. Therefore, selection of asymptomatic patients based on their respective 'high-risk features' ( table 4 ) for CR would be reasonable and beneficial to prevent stroke [23,39,41,42] .…”
Section: Decision-making On Management Of Carotid Stenosismentioning
confidence: 99%
“…However, these data should be interpreted with caution, because they were conducted before the introduction of optimized medical treatment. The latter includes antiplatelets, statins, control of blood pressure and blood glucose level, smoking cessation, implementation of exercise programs, Mediterranean diet, and lifestyle modification, and was shown to significantly reduce the stroke risk among patients with asymptomatic ICA-stenosis (30, 31). Current optimized medical treatment is an established therapy for prevention of arterial disease complications, including patients with carotid stenosis, whether mild or severe, and it is a continually improving gold standard of care (32, 33), and should also be offered perioperatively before CEA (34).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery revascularization in patients with asymptomatic stenosis raises consider-able doubts, which stems from the low estimated risk of stroke related to asymptomatic lesions. This risk is often believed not to exceed the risk of stroke associated with revascularization therapy alone [8,18,22,31,32].…”
Section: Introductionmentioning
confidence: 99%